DIGITAL TRANSFORMATION AND ORGANIZATIONAL DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW ON STRUCTURAL ADAPTATION, PROCESS INNOVATION, AND CULTURAL READINESS - Maria Sampe; Sahrun Asis; Ade Bukti Ramadhan; Syahril; Tetra Hidayati (RADJA PUBLIKA, 2025)
Digital transformation has emerged as a significant catalyst for change within contemporary organizations, necessitating modifications to strategy, structure, processes, and work culture. This study explores the relationship between digital transformation and organizational development (OD) by emphasizing three critical dimensions: structural adaptation, process innovation, and organizational cultural readiness. Employing a systematic literature review methodology, this study analyzed 25 scholarly articles published between 2021 and 2025. Articles were selected from reputable databases such as Scopus, ScienceDirect, Emerald Insight, and Taylor & Francis based on criteria including publication in indexed journals, a focus on digital transformation and organizational development, and the use of both empirical and conceptual approaches. The findings indicate that the success of digital transformation is contingent on the integration of organizational restructuring, renewal of work processes, and establishment of a technology-adaptive culture. Structural adaptation enhances organizational agility and effectiveness through decentralization and cross-functional collaborations. Process innovation bolsters efficiency and productivity through the digitalization of work systems and enhancement of human resource competencies. Organizational cultural readiness contributes to the sustainability of transformation through continuous learning, digital leadership and team collaboration. This study confirms that organizational development in the digital era no longer prioritizes administrative efficiency but focuses on cultivating adaptive and innovative capabilities that reinforce organizational resilience. Theoretically, this study proposes a Digital Organizational Development (DOD) framework that integrates these three key dimensions as a model for modern organizational development. Practically, the study's findings offer guidance for organizations to balance technology strategies with structural and cultural interventions to achieve effective and sustainable digital transformation.